2017
DOI: 10.1101/141648
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Alpha oscillations during incidental encoding predict subsequent memory for new “foil” information

Abstract: People can employ adaptive strategies to increase the likelihood that previously encoded information will be successfully retrieved. One such strategy is to constrain retrieval towards relevant information by re-implementing the neurocognitive processes that were engaged during encoding. Using electroencephalography (EEG), we examined the temporal dynamics with which constraining retrieval towards semantic versus non-semantic information affects the processing of new "foil" information encountered during a mem… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 61 publications
(98 reference statements)
0
9
0
Order By: Relevance
“…Despite the long history of M/EEG studies on recognition memory (Sanquist et al, 1980; for reviews, see Mecklinger, 2000; Rugg and Curran, 2007), only a few have examined oscillatory patterns related to different memory outcomes (Burgess & Gruzelier, 2000; Khader & Rösler, 2011; Michelmann, Bowman, & Hanslmayr, 2016; Vogelsang, Gruber, Bergström, Ranganath, & Simons, 2018; Waldhauser, Braun, & Hanslmayr, 2016), albeit without explicitly distinguishing associative recall from item recognition. Our current paradigm allowed us to directly probe the oscillatory mechanisms that support these different memory signals (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Despite the long history of M/EEG studies on recognition memory (Sanquist et al, 1980; for reviews, see Mecklinger, 2000; Rugg and Curran, 2007), only a few have examined oscillatory patterns related to different memory outcomes (Burgess & Gruzelier, 2000; Khader & Rösler, 2011; Michelmann, Bowman, & Hanslmayr, 2016; Vogelsang, Gruber, Bergström, Ranganath, & Simons, 2018; Waldhauser, Braun, & Hanslmayr, 2016), albeit without explicitly distinguishing associative recall from item recognition. Our current paradigm allowed us to directly probe the oscillatory mechanisms that support these different memory signals (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…This strategy thus involves focusing on semantic aspects of stimuli ("deep" processing) in a recognition test if the initial encoding task involved semantic judgements, versus focusing on perceptual aspects of stimuli ("shallow" processing) if the initial encoding task involved perceptual judgements. By reinstating such different processing modes, the foils become more deeply encoded in the deep test than the shallow test (see Danckert, et al, 2011;Gray & Gallo, 2015;Jacoby, Shimizu, Daniels, et al, 2005;Vogelsang et al, 2016Vogelsang et al, , 2018.…”
Section: Discussionmentioning
confidence: 99%
“…The experiment was programmed and run in PsychoPy (Peirce et al, 2019;Peirce, 2007) on a tablet computer. In total 288 English words from the MRC psycholinguistic database (Wilson, 1988) were used as stimuli (3-11 characters, Kucera-Francis frequency range 0-591), drawn from a larger set used by Vogelsang et al (2016Vogelsang et al ( , 2018. The words were randomly split into twelve lists of 24 words each, with assignment to experimental conditions counterbalanced across participants (see procedure for details).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, previous studies have shown that encoding-related brain activity (i.e., predictive of subsequent memory) is shaped both by the type of processing occurring at encoding and by the overlap between encoding and retrieval processes (Bauch and Otten, 2012; Fellner et al, 2013; Staudigl and Hanslmayr, 2013; Vogelsang et al, 2016; 2018; Long and Kahana, 2017). The typical procedure in these previous studies has been to investigate encoding-related brain activity when explicitly instructing participants to attend to particular attributes during the encoding and retrieval.…”
Section: Introductionmentioning
confidence: 99%